100 things to know about Numbers, Computers & Coding - James, Alice (London : Usborne Publishing Ltd, 2018)
When was the webcam invented and why? Do imaginary numbers exist? What is fuzzy logic? Find the answers these questions about the amazing world of numbers, computers and coding, along with loads of other curious, amazing and mind-boggling facts, in this eye-catching book that is absolutely bursting with information
Keywords: Coding theory; Computer programming